COMPLEX EVALUATION OF WORKING CONDITIONS IN WORKSHOPS OF METAL HEAT TREATMENT - A. M. Lazarenkov; S. A. Khoreva; V. V. Melnichenko (Литьë и металлургия)
The results of complex evaluation of working conditions in workshops of metal heat treatment, and based on research of industrial environmental factors jobs are given. The hygienic overview of working conditions classification in working stations of metals heat treatment shops is given.